Pengaruh Literasi Digital Terhadap Berpikir Kritis Mahasiswa Dalam Pembelajaran - Novia Marwiah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study examines how digital literacy influences students’ critical thinking skills in the educational process during the digital era. The research used a literature review method by analyzing various scientific publications related to digital literacy and critical thinking. The findings indicate that digital literacy has a positive and significant effect on students’ critical thinking abilities. Students with higher digital literacy skills are more capable of accessing, analyzing, evaluating, and using information effectively. Digitally literate students can also identify reliable information sources, avoid misinformation and scams, and make logical decisions and plans. In addition, technologies such as social media and artificial intelligence can support learning when accompanied by strong analytical skills. Therefore, the ability to use digital tools effectively is essential for modern educators who aim to improve learning quality and enhance student achievement in today’s digital learning environment. These findings highlight the importance of integrating digital literacy instruction into educational practices at all learning levels.